Fenomena Pernikahan Anak Usia Dini sebagai Penyimpangan Budaya Indonesia - Gusnita, Chazizah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Indonesia has many cultures that are prone to violence and deviation. This problem becomes an important focus in this study because this cultural’s deviation involved children in it. Indonesia has the second highest child marriage rate in ASEAN after Cambodia and ranks 37th overall in the world. This study described the circumstances, conditions, situations, events, and activities as well as the support of community leaders in legalizing early childhood marriage in South Nias as a case study. The phenomenon of early marriage culture in South Nias, especially in Hilinamoniha village, is still happening and has become a natural and normal thing for the local community. Adat which is still very strong shifts the position of the government as the highest peak of power in a village. Traditional leaders as customary holders who give permission for a marriage to take place are the key for the community to continue to be brave and willing to marry off their children must be underage. Parents who marry off their children are also another major factor in the occurrence of early marriage. This research uses rational theory with qualitative descriptive method